THE IMPACT OF TOURISM OBJECTS ON BUSINESS OPPORTUNITIES AND INCOME OF LOCAL TRADERS IN TAMAN RINJANI SELONG - Laela Patmawati; Muhamad Yusup (SEAN Institute, 2023)
The impact of tourism objects on business opportunities and income of local traders in Rinjani Selong Park is considered necessary to be researched. This is related to the impact in improving the economy of local traders in Rinjani Selong Park which was felt after the existence of a tourist attraction when there was no tourist attraction. So in this study the researcher tried to collect data regarding matters relating to the impact of tourism objects on business opportunities and income of local traders around the Rinjani Selong park. The method used in this research is the filed research method (field research) using field methods of interviews, observation, and documentation as data collection instruments, as well as using interactive analysis by reducing data, presenting data, and drawing conclusions to analyze the data that has been obtained. from the results of research in the field. Meanwhile, the results of the research conducted by researchers are that the impact or influence of tourism in creating business opportunities and improving the economy of local traders in Rinjani Selong Park has had a significant impact both in improving the economy of traders and in creating business opportunities there. This can be seen from the number of businesses run by local communities and the fulfillment of the basic needs of traders and also some traders have been able to buy more than basic needs, such as buying motorbikes and even cars and so on obtained from the results of businesses run at tourist attractions.